Disordered domains in chromatin-binding proteins. Issue 1 (2nd April 2019) - Watson, Matthew; Stott, Katherine
Abstract : Chromatin comprises proteins, DNA and RNA, and its function is to condense and package the genome in a way that allows the necessary transactions such as transcription, replication and repair to occur in a highly organised and regulated manner. The packaging of chromatin is often thought of in a hierarchical fashion starting from the most basic unit of DNA packaging, the nucleosome, to the condensation of nucleosomal 'beads on a string' by linker histones to form the 30-nm fibre and eventually large chromatin domains. However, a picture of a more heterogeneous, dynamic and liquid-like assembly is emerging, in which intrinsically disordered proteins (IDPs) and proteins containing intrinsically disordered regions (IDRs) play a central role. Disorder features at all levels of chromatin organisation, from the histone tails, which are sites of extensive post-translational modification (PTM) that change the fate of the underlying genomic information, right through to transcription hubs, and the recently elucidated roles of IDPs and IDRs in the condensation of large regions of the genome through liquid–liquid phase separation.